Quality of life in patients with calluses - Demir, Betul; Cicek, Demet; Erden, Ilker; Ucak, Haydar; Demir, Sukru; Ozturk, Savas (Wiley-Blackwell, 2016)
[Abstract Not Available]
Keywords: Foot; Prevalence; Health; Corns